Elevation of Pectobacterium carotovorum subsp. odoriferum to species level as Pectobacterium odoriferum sp. nov., proposal of Pectobacterium brasiliense sp. nov. and Pectobacterium actinidiae sp. nov., emended description of Pectobacterium carotovorum and description of Pectobacterium versatile sp. nov., isolated from streams and symptoms on diverse plants. Issue 10 (25th July 2019) - Portier, Perrine; Pédron, Jacques; Taghouti, Géraldine; Fischer-Le Saux, Marion; Caullireau, Emma; Bertrand, Claire; Laurent, Angélique; Chawki, Khaoula; Oulgazi, Saïd; Moumni, Mohedine; Andrivon, Didier; Dutrieux, Cécile; et al.
Abstract : The Pectobacterium carotovorum species corresponds to a complex, including two subspecies with validly published names, two proposed subspecies and two new species, Pectobacterium polaris and Pectobacterium aquaticum . Recent studies suggested that this complex needed revision. We examined the taxonomic status of 144 Pectobacterium strains isolated from a wide range of plant species, various geographical origins and waterways. Sequences of the leuS, dnaX and recA housekeeping genes clustered 114 of these Pectobacterium strains together within a not yet described clade. We sequenced eight strains of this clade and analysed them together with the 102 Pectobacterium genomes available in the NCBI database. Phylogenetic analysis, average nucleotide identity calculation and in silico DNA–DNA hybridization allowed us to differentiate seven clades. This led us to propose the elevation of Pectobacterium carotovorum subsp. odoriferum to species level as Pectobacterium odoriferum sp. nov. (type strain CFBP 1878 T =LMG 5863 T =NCPPB 3839 T =ICMP 11533 T ), the proposal of Pectobacterium actinidiae sp. nov. (type strain KKH3=LMG 26003 T =KCTC 23131 T ) and Pectobacterium brasiliense sp. nov. (type strain CFBP 6617 T = LMG 21371 T =NCPPB 4609 T ), to emend the description of Pectobacterium carotovorum (type strain CFBP 2046 T =LMG 2404 T =NCPPB 312 T =ICMP 5702 T ), and to propose a novel species, Pectobacterium versatile sp. nov (type strain CFBP6051 T = NCPPB 3387 T =ICMP 9168 T ) which includes the strains previously described as 'Candidatus Pectobacterium maceratum '. Phenotypic analysis performed using Biolog GENIII plates on eight strains of P. versatile sp. nov. and related strains completed our analysis.